If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B = 2x(3x + -4) Reorder the terms: B = 2x(-4 + 3x) B = (-4 * 2x + 3x * 2x) B = (-8x + 6x2) Solving B = -8x + 6x2 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Simplifying B = -8x + 6x2
| 4s^2+s-14=0 | | 630=0.03*3 | | -5+x^2+12x+40=0 | | 3(5m-2)=15m-6 | | 9x^3-4x= | | 37+2y-12y=-10-5y | | x^2+x+41=y^2 | | 3(3b-8)= | | 2x+6+2x-11+x=180 | | 6-3a=5a-qpa+18 | | -6=-6(-3+p) | | 9x^2+54x+9y^2-6y=-64 | | 7y+15=14y+57 | | 8(0)-5y=40 | | 16.5+3t=0.9-t | | 37+2y-12=-10-5y | | 3(k+2)+10=46 | | -3=5-h | | 5x-3-7x=4-10x+5 | | 0.5x+14forx=23 | | 4+2w=w-10 | | 16x-1(4-5x)=67 | | -6+7x=7x-1 | | 44-1+7d=106 | | -6-2+2x=x-2x-7+19 | | 7(7x+10)=49x-2 | | 12(x-2)=2(6x-1)-22 | | 33=8+5d | | x(2x-1)=3x+4 | | -5t^2+30t=24 | | 6+35=15x+54 | | -16-20=-14x+70 |